Dictionary of the English language - Johnson, Samuel, 1709-1784 (Arno Press, 1979)
A dictionary with more than 40,000 entries which was a primary reference source for scholars and writers of the 18th and 19th century
Reprint of the 1755 ed. printed by W. Strahan, London
Keywords: English language -- Dictionaries